The Complete Chloroplast Genome Analysis Of Cinnamomum Cassia Presl - Jiang, Shaofeng; Liu, Yingying; Cui, Shan; Gui, Lingjian; Huang, Jinqing (Bangladesh Journal of Botany, 2022)
Cinnamomum cassia Presl is widely known as an important aroma and medicinal tree species growing in tropical and subtropical regions of Asia. The complete chloroplast genome of C. cassia which is 152,763 bp in length was determined. A total of 126 genes were detected in the chloroplast genome, including 36 tRNA genes, 8 rRNA genes, and 82 CDS. The total number of SSRs in this genome is 157. Phylogenetic analysis of this species based on 51 shared chloroplast CDS is provided. These results will provide useful resources for the study of molecular phylogeny and genetics of C. cassia. Bangladesh J. Bot. 51(1): 51-55, 2022 (March)